Pengaruh Customer Relationship Management dan Customer Experience Quality Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Studi Pada Konsumen di Sisha Cafe Kemang) - Wasi Bagasworo; Visi Hardiani (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
This study discusses the customer relationship management and quality of the customer experience, which is thought to affect customer satisfaction and the impact on customer loyalty at sisha cafe Kemang. In this study, the variable of the customer relationship management and the customer experience quality is measured through the dimensions of those variables. Each of these dimensions will be partially tested on how it affects customer satisfaction and customer loyalty. In addition, this study also wanted to know which the most influential dimension to customer satisfaction and customer loyalty are. The research sample was 100 visitors who visited the sisha cafe Kemang at least three times within a period of one week. The observations will be analyzed using the Structural Equation Model (SEM). The results from the study showed that the four dimension of customer relationship management and five dimensions of customer experience quality have a strong significant effect on customer satisfaction. and so it takes customer satisfaction as an intervening variable to achieve customer loyalty have a strong significant effect.